Liposomal doxorubicin loaded PLGA-PEG-PLGA based thermogel for sustained local drug delivery for the treatment of breast cancer - Dinglingge Cao; Xingxian Zhang; MD. Akabar; Yuan Luo; Hao Wu; Xue Ke; Tianyuan Ci (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
The aim of this research is to utilize a hybrid system of liposomal doxorubicin (DOX-Lip) loaded thermogel (DOX-Lip-Gel) to realize the steady sustained delivery of doxorubicin (DOX), a small hydrophilic drug, for the treatment of breast cancer locally. Herein, liposomal doxorubicin was prepared via the traditional film dispersion method with the particle size of 75 nm and drug entrapment efficiency of 86%. And, the triblock copolymer of poly (D, L-lactide-co-glycolide)-b-poly (ethylene glycol)-b-poly (D, L-lactide -co-glycolide) (PLGA-PEG-PLGA) was synthesized via ring-opening polymerization to prepare the thermosensitive hydrogel through dissolving the polymers in DOX-Lip solution. The liposome loaded hydrogel was in a sol state at room temperature and converted into the gel state at body temperature and would degrade gradually during the time in vivo. The drug release of DOX out of DOX-Lip-Gel could be in a steady sustained manner up to 11 days without significant burst release as compared to that of DOX-loaded hydrogel (DOX-Gel). An orthotopic breast cancer model was adopted to evaluate the in vivo antitumor efficacy. And, the results revealed DOX-Lip-Gel had better antitumor efficiency as well as lower side effects.